Minimizing Patient Safety Events Through a Multidisciplinary Approach to Human Milk Management. (October 2015) - Paul, Elizabeth
Optimization of nutrition is key in infant development and it is well documented that human milk is the ideal form of nutrition for infants during the first year of life. However, unaltered maternal human milk may not be sufficient to meet the nutritional demands of premature infants. Under these circumstances, addition of a fortifier to the maternal human milk has become standard practice. In one newborn/infant intensive care unit (N/IICU) located in Philadelphia, fortification and modification of human milk is handled within the Human Milk Management Center (HMMC). A multidisciplinary team rounds weekly on all infants receiving fortified or modified human milk. Feeding orders and maternal milk supply are discussed to ensure the feeding is ordered correctly, the final caloric concentration is correct and a backup feeding order is in place for low maternal milk supply. Through this multidisciplinary discussion, the team has been able to identify and resolve potential errors from reaching the patient. Improvement in patient safety while providing human milk remains of utmost importance and the central goal of the HMMC collaborative.